1992
DOI: 10.1111/j.1365-2621.1992.tb06842.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphates and Muscle Fiber Type Influence Thermal Transitions in Porcine Salt‐Soluble Protein Aggregation

Abstract: Salt-soluble proteins (SSP) were extracted from porcine Serratus ventralis (red), Vastus intermedius (red) and Longissimus dorsi (white) muscles and heated to examine dynamic changes and transitions in protein aggregation. At pH 6.0, red muscle SSP typically showed 1 or 2 transitions and white muscle SSP exhibited 3 transitions. Addition of ortho-, pyro-, tripoly-and hexametaphosphate up to 1% increased SSP transition temperatures and altered transition patterns; NaCl at comparable ionic strengths did not show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Electrophoresis was run at constant current with a PowerPac 300 power supply (Bio-Rad Laboratories, Hercules, CA, USA). The initial current was 20 mA per gel then raised to 40 mA per gel after samples entered the separating gel (Robe & Xiong, 1992).…”
Section: Sdsepolyacrylamide Gel Electrophoresis (Sdsepage)mentioning
confidence: 99%
“…Electrophoresis was run at constant current with a PowerPac 300 power supply (Bio-Rad Laboratories, Hercules, CA, USA). The initial current was 20 mA per gel then raised to 40 mA per gel after samples entered the separating gel (Robe & Xiong, 1992).…”
Section: Sdsepolyacrylamide Gel Electrophoresis (Sdsepage)mentioning
confidence: 99%
“…Because it imparts bitter taste notes when used in excessive amounts, KCl concentrations lower than 50% in meat formulations has been recommended for sodium chloride replacement (Ruusunen and Puolanne ). One other possible alternative in reducing sodium chloride in meat systems is the use of alkali phosphates, which have been used as curing agents to improve protein extraction, resulting in better protein functionality with subsequent improvement of textural properties of the products (Robe and Xiong ; Price ; Lampila and Godber ). Thus, the aim of the present study was to evaluate the effects of partial substitution of NaCl with KCl in the presence of sodium tri‐polyphosphate (STPP) on the textural, rheological and water binding properties of SSMP gels from beef Semimembranosus muscles.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that the use of PHSDEW‐DH3% increased the thermal resistance of the myosin and actin. Several studies had proved that phosphates could decrease the heat stability of the shrimp muscle proteins (Robe & Xiong, ). T max increment might be attributed to the rearrangement of water molecules around the protein molecules, which resulted in a slight increase in hydrophobic interactions (Medina‐Vivanco et al ., ).…”
Section: Resultsmentioning
confidence: 99%